Ethnobiology, Political Ecology, and Conservation. Issue Volume 34:Issues 2(2014) (July 2014) - Wolverton, Steve; Nolan, Justin M.; Ahmed, Waquar
Ethnobiology is increasingly recognized from within and outside of its boundaries as interdisciplinary. The Society of Ethnobiology defines the field as "the scientific study of dynamic relationships among peoples, biota, and environments." Ethnobiologists are able to skillfully assess challenges of biocultural conservation across the divides of political ecology. They are situated to mediate between conservation programs that target biodiversity preservation with little concern for the needs of human communities, and those (such as the New Conservation movement) that privilege those needs. Ethnobiology also transcends the pervasive assumption in these fields that Western knowledge and economic goals should guide change. Because of ethnobiology's importance as a bridging discipline, it is important to ask what unifies ethnobiology. Is it common subject matter? Or, is there an underlying emphasis representing an "ethnobiological perspective?" Answers to these questions are explored here using content analysis and discourse-and-ideology analysis. We use the results to identify the unique roles ethnobiologists play in biocultural conservation. This analysis also proved useful in the systematic identification of four salient themes that unify ethnobiology—ethics in ethnobiology, shared environmental and cultural heritage, interdisciplinary science and non-science, and ecological understanding. How ethnobiologists conceive of themselves is critical for further enrichment of the field as interdisciplinary human-environmental scholarship, particularly in reference to biocultural conservation. Self-definition makes explicit the unique strengths of the field, which by its very nature integrates a sophisticated understanding of political ecology with appreciation of the value of traditional ecological knowledge (TEK), social science, and the biological sciences.